THE RELATIONSHIP BETWEEN SELF-EFFICACY AND SPEAKING ANXIETY AMONG PGSD STUDENTS IN ASSISTING ENGLISH SPEAKING LESSONS AT THE ELEMENTARY LEVEL - Rifhani Handayani L; Faidah Yusuf; A. Muh. Ali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigated the relationship between self-efficacy and speaking anxiety among students of the Primary School Teacher Education (PGSD) program in assisting English speaking lessons at the elementary level. Employing a quantitative correlational design, data were collected from 83 students of the 2023 PGSD cohort at Universitas Negeri Makassar, selected through simple random sampling using Slovin’s formula. Two validated instruments were used: the Self-Efficacy Scale and the Speaking Anxiety Scale, both showing good reliability (α = .82 and .79). Data analysis involved descriptive statistics, Pearson’s correlation, and Kendall’s tau-b. The findings revealed a significant negative correlation between self-efficacy and speaking anxiety (r = –.290, p = .008; τ = –.252, p = .002), indicating that students with higher self-efficacy tended to experience lower levels of speaking anxiety. These results emphasize the critical role of affective factors in pre-service teacher preparation, particularly within structured programs such as Asistensi Mengajar di Satuan Pendidikan (AMSD), Pengenalan Lapangan Persekolahan (PLP) 1, and PLP 2, where PGSD students serve as teaching assistants. The study suggests that pedagogical strategies such as microteaching, peer collaboration, and reflective practice may enhance self-efficacy and reduce speaking anxiety, thereby improving pre-service teachers’ readiness to support English speaking instruction at the elementary level.